2021
DOI: 10.3390/met11101538
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Properties of Nitrocarburizing S-Phase on AISI 316L Stainless Steel-Based WC Composite Layers by Low-Temperature Plasma Nitriding

Abstract: Stainless steel-based WC composite layers fabricated by a laser cladding technique, have strong mechanical strength. However, the wear resistance of WC composite layers is not sufficient for use in severe friction and wear environments, and the corrosion resistance is significantly reduced by the formation of secondary carbides. Low-temperature plasma nitriding and carburizing of austenitic stainless steels, treated at temperatures of less than 450 °C, can produce a supersaturated solid solution of nitrogen or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Some studies have shown that surface laser treatment can significantly increase the thickness and hardness of the nitrided layer and form a more uniform nitrided layer structure [196]. Surface laser treatment can also promote the formation of precipitates in the nitrided layer, which further increases hardness and wear resistance [197]. When the nitriding temperature is increased from 500 • C to 560 • C, the surface hardness increases by about 55%.…”
Section: Effect Of Surface Laser Treatment On Nitriding Efficiencymentioning
confidence: 99%
“…Some studies have shown that surface laser treatment can significantly increase the thickness and hardness of the nitrided layer and form a more uniform nitrided layer structure [196]. Surface laser treatment can also promote the formation of precipitates in the nitrided layer, which further increases hardness and wear resistance [197]. When the nitriding temperature is increased from 500 • C to 560 • C, the surface hardness increases by about 55%.…”
Section: Effect Of Surface Laser Treatment On Nitriding Efficiencymentioning
confidence: 99%
“…Expanded austenite was observed to form not only in austenitic stainless steels, both in massive specimens [8,11,46,47,146] and coatings obtained with various techniques [147][148][149][150][151][152][153][154], but also in stainless steels, in which the high N solubilization might induce the transformation of ferrite or martensite into austenite, as duplex [104,116,132,[134][135][136], martensitic [65,91,95], ferritic [121,122], and precipitation hardening [65,71,155,156] stainless steels.…”
Section: Expanded Austenite-s-phasementioning
confidence: 99%
“…Thus, high corrosion resistance is maintained, and pitting corrosion in chlorinated environments is inhibited [19][20][21][22][23][24][25][26][27][28]. In a previous study, AISI 316L stainless-steel-based tungsten carbide composite layers fabricated via laser metal deposition were subjected to low-temperature plasma nitriding, and the formation of the S phase was confirmed at temperatures of 400-450 • C and a processing time of 4 h [29]. The hardness of the stainless-steel parts in the composite layers increased from 500-700 HV to 1200-1400 HV.…”
Section: Introductionmentioning
confidence: 97%
“…A few papers have reported low-temperature nitriding and carburizing for austenitic stainless-steel fabrication via directed energy deposition and powder bed fusion [22,24,32,46,47]. However, to the best of our knowledge, none of the studies published to date investigate tungsten carbide composites except the previous study [29]. The effect of original solidsolution carbon present in stainless-steel plates on low-temperature nitriding has been well-researched in previous studies, establishing the formation of thin carburizing S phase layers at the interface between the nitriding layer and substrate [21,26,48,49].…”
Section: Introductionmentioning
confidence: 99%